Does productivity affect profitability in dairy processing industry? Evidence from Slovenia, Croatia and Serbia - Saša Muminović; Željana Aljinović Barać (Mljekarstvo)
This paper provides insights into productivity in dairy processing companies in Slovenia, Croatia and Serbia. The aim is to find out whether EBITDA per employee, as a measure of overall productivity as well as labour and capital productivity and their management positively affect company’s profitability. Literature review shows that this issue was relatively neglected, although increase in productivity is regarded as the most important factor in maintaining a competitive advantage in most developed countries. Results obtained show that comprehensive measure of productivity EBITDA per employee has statistically significant positive impact on company’s profitability, the same as productivity management components labour cost competitiveness and capital productivity.